2021
DOI: 10.1111/mpp.13105
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic interaction between the type III secretion system of the endophytic bacterium Pantoea agglomerans DAPP‐PG 734 and the virulence of the causal agent of olive knot Pseudomonas savastanoi pv. savastanoi DAPP‐PG 722

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…As already hypothesized in the previous study [22], it was confirmed from the complete genome sequence that the Hrp-1 T3SS of P. agglomerans DAPP-PG 734 (DAPPPG734_23535-DAPPPG734_23710) is located on a large, 174′327-bp plasmid, here called plasmid 2 (Fig. 4).…”
Section: Plasmid 2 Carrying the Hrp-1 Type III Secretion Systemsupporting
confidence: 74%
See 4 more Smart Citations
“…As already hypothesized in the previous study [22], it was confirmed from the complete genome sequence that the Hrp-1 T3SS of P. agglomerans DAPP-PG 734 (DAPPPG734_23535-DAPPPG734_23710) is located on a large, 174′327-bp plasmid, here called plasmid 2 (Fig. 4).…”
Section: Plasmid 2 Carrying the Hrp-1 Type III Secretion Systemsupporting
confidence: 74%
“…The pan-genomic analysis revealed that the gene cluster for T3SS in P. agglomerans DAPP PG 734 (Hrp-1 T3SS) has, next to the Hrp structural system, a complete Hrp effectors and elicitors (HEE) region [22]. This gene cluster was similar to the corresponding gene clusters of Pantoea stewartii subsp.…”
Section: Plasmid 2 Carrying the Hrp-1 Type III Secretion Systemmentioning
confidence: 84%
See 3 more Smart Citations